Chemical constituents from the branches of Broussonetia papyrifera and their chemotaxonomic significance - Gao, Cong-Xi; Ma, Wen-Jie; Chen, Wu-Yan; Shi, Hong-Ji; Tian, Ding; Hu, Jian-Lin; Wang, Kou (Biochemical systematics and ecology, 2025)
Phytochemical investigation of the branches of Broussonetia papyrifera (Moraceae) resulted in the isolation of thirty-one compounds, including: nine flavans (1–9), five diarylpropanoids (10–14), three steroids (15–17), two anthraquinones (18, 19), two hydroxybenzoic acids (20, 21), three terpenoids (22, 25, 27), six phenylpropanoids (23, 24, 26, 29–31), and one heterocyclic compound (28). Among them, seven compounds (1, 9, 10, 13, 14, 23, and 31) were isolated from the Moraceae family for the first time. Evaluation of the flavan and diarylpropanoid compounds (1–14) for anti-atopic dermatitis (AD) activity demonstrated that eight compounds inhibited IL-13 secretion in HaCaT cells. Notably, compounds 2, 10, and 12 displayed the most potent activity, reducing IL-13 secretion below levels achieved by the positive control dexamethasone. Furthermore, the chemotaxonomic significance of the isolated constituents is discussed in detail. [Display omitted] •Thirty-one compounds were identified from the branches of Broussonetia papyrifera.•Seven compounds were reported in the Moraceae family for the first time.•Eight compounds exhibited significant anti-atopic dermatitis activity.•The chemotaxonomic significance of these compounds was discussed.